Damping ratios identification by sensitivity-based model updating: Experimental investigation - Li, Jun; Hao, H.; Fan, G. (2017)
Identification of damping characteristics is of significant importance for dynamic response analysis and condition assessment of structural systems. Damping is associated with the behavior of the energy dissipation mechanism. Identification of damping ratios based on the sensitivity of dynamic responses and the model updating technique is investigated with experimental investigations. The effectiveness and performance of the sensitivity-based model updating method for damping ratios identification are investigated. Experimental studies on a steel planar frame structure are conducted. The robustness and performance of the proposed damping identification approach considering noise effect and modelling errors are investigated. The results demonstrate that the proposed approach has a decent and reliable performance to identify the damping ratios based on time domain analysis.